2006
DOI: 10.1111/j.1525-1314.2006.00649.x
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing P–T paths during continental collision using multi‐stage garnet (Gran Paradiso nappe, Western Alps)

Abstract: International audienceGarnet-chloritoid-bearing micaschists from the Gran Paradiso massif (Western Alps) contain evidence of a polymetamorphic evolution. Detailed textural observations reveal that two stages of garnet growth are present in the micaschists, interpreted as: (i) relics of an early metamorphism of pre-Alpine age and (ii) newly grown Alpine garnet, respectively. Both generations of garnet preserve growth zoning. Fromthermocalc-based numerical modelling of mineral assemblages in pressure-temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 52 publications
(77 reference statements)
4
69
2
2
Order By: Relevance
“…A deep burial (around 50 km) for rocks located in the East (Ruitor and Internal units) similar to the neighbouring rocks of the Gran Paradiso (60 km, Le Bayon et al 2006) and of the Piemont-Ligurian ocean (50-60 km, Bousquet 2007) and a shallow burial (around 10 km) for rocks located in the East, in contrast to the rocks of the Valaisan ocean that were buried at great depths (50 km, Bousquet et al 2002). A major tectonic contact, acting top-tothe-northwest during exhumation of HP rocks has separated the two groups.…”
Section: Discussion-conclusionmentioning
confidence: 99%
“…A deep burial (around 50 km) for rocks located in the East (Ruitor and Internal units) similar to the neighbouring rocks of the Gran Paradiso (60 km, Le Bayon et al 2006) and of the Piemont-Ligurian ocean (50-60 km, Bousquet 2007) and a shallow burial (around 10 km) for rocks located in the East, in contrast to the rocks of the Valaisan ocean that were buried at great depths (50 km, Bousquet et al 2002). A major tectonic contact, acting top-tothe-northwest during exhumation of HP rocks has separated the two groups.…”
Section: Discussion-conclusionmentioning
confidence: 99%
“…The occurrence of multi-stage garnet is a common feature of polymetamorphic/polycyclic terrains (Rumble and Finnerty 1974;Karabinos 1984;Madhjoub et al 1997;Vry et al 2004;Zulbati and Harley 2007) and many occurrences have been reported from pre-Alpine basement complexes of the Alps (Dal Piaz 1963;Droop 1981;von Raumer and Schwander 1985;Borghi and Sandrone 1995;Matsumoto and Hirajima 2000;Dachs and Proyer 2001;Faryad and Hoinkes 2003;Ganne et al 2003;Faryad and Chakraborty 2005;Le Bayon et al 2006). The two garnet populations (C-Grt and F-Grt 3 ) of the Am-schist AD379A described above belong to a microstructural domain which equilibrated during D3.…”
Section: Interpretation Of the Bimodal Garnet Population Of The Am-scmentioning
confidence: 96%
“…2). Pressure conditions for the development of the mylonitic lineation were estimated to be 8 AE 3 kbar, whereas the temperature was estimated to be 450e500 C by Borghi et al (1996) and Le Bayon et al (2006a;2006b) and 550e600 C by Gasco and Borghi (2011).…”
Section: Sample Description: Mesostructures Microstructures and Chemmentioning
confidence: 97%